SYNTHESIS, STRUCTURAL STUDIES AND ACETYLCHOLINESTERASE INHIBITION ACTIVITY OF SOME (E)-2-METHOXY-3-NITRO-4-(3-OXO-3-ARYLPROP-1-EN-1-YL)PHENYL ACETATES - Minh Lương, Truong (HNUE Journal of Science: Journal of Natural Sciences, 2025)
A semi-synthetic process from vanillin (isolated from vanilla) was developed to obtain new esters with potential inhibitory activity against the acetylcholinesterase (AchE.). 2-Nitrovanillin was synthesized from vanillin by esterification, nitration, and hydrolysis reactions. Four chalcones were synthesized by acid-catalyzed condensation reaction of 2-nitrovanillin and methyl aryl ketone. The identity of 2-nitrovanillin and four chalcones was confirmed by thin-layer chromatography compared with the known compounds. Subsequent esterification of the chalcones with acetic anhydride yielded four new derivatives of (E)-2-methoxy-3-nitro-4-(3-oxo-3-(aryl)prop-1-en-1-yl)phenyl acetate. The structures of the four new compounds were elucidated by 1H NMR and 13C NMR spectra. The four compounds were evaluated for their inhibitory activity against AChE. and three of them exhibited significant activity.